A Thermometer Based on Er‐Sensitized Phosphors Gd2(WO4)3:Er, Yb@SiO2 in Near‐Infrared and Visible Regions. Issue 6 (17th March 2020) - Wang, Huayao; Sun, Zhen; Wei, Yanling; Jia, Mochen; Hou, Bofei; Li, Xin; Lin, Fang; Zhang, Mingxuan; Xu, Yang; Fu, Zuoling
Abstract : Currently, the ratiometric temperature sensing based on thermally coupled levels and nonthermally coupled levels dominates the optical thermometers. Herein, Gd2 (WO4 )3 :Er, Yb@SiO2 phosphors are successfully synthesized by the one‐pot coprecipitation method. The themperature sensing properties based on fluorescence intensity ratio (FIR) at 808 nm excitation are investigated in detail. In the visible region, the maximum relative sensitivity ( S r ) of 0.0112 K −1 based on thermally coupled energy levels of Er 3+ ( 2 H11/2 and 4 S3/2 ) is achieved at 323 K, whereas the maximum of S r based on nonthermally coupled energy levels of Er 3+ ( 4 I13/2 ) and Yb 3+ ( 2 F5/2 ) in the near‐infrared region is 0.0035 K −1 at the lowest temperature 303 K, indicating that the thermometer can be used in the biological temperature range. Moreover, to determine which kind of thermal sensing method is more reliable, the relative standard deviation (RSD) is calculated. In comparison, it is confirmed that temperature sensing based on thermally coupled levels is more stable. Abstract : A thermometer in the visible and near‐infrared region is developed based on Er‐sensitized Gd2 (WO4 )3 :Er, Yb@SiO2 phosphors. The sensitivity of the thermometer based on both thermally (in the visible region) and nonthermally (in the near‐infrared region) coupled levels of the rare‐earth ions is high, indicating that Gd2 (WO4 )3 :Er, Yb@SiO2 phosphors have potential applications in biological temperature sensing.